2021
DOI: 10.1029/2020jd033720
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion of Droplet Size Distributions in Supercooled Non‐precipitating Stratocumulus from Aircraft Observations Obtained during the Southern Ocean Cloud Radiation Aerosol Transport Experimental Study

Abstract: These low-level clouds, such as shallow boundary layer clouds (e.g., subtropical stratocumulus and trade-wind cumulus) have significant impacts on the radiation budget and climate change (Bony & Dufresne, 2005). While most past studies have focused on r e and LWC, the relative dispersion (ε), defined as the ratio of the standard deviation of the droplet size distribution (σ) to the number mean radius (r m), represents another DSD parameter which is of great importance to estimate the indirect aerosol effect on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 82 publications
(155 reference statements)
4
17
0
Order By: Relevance
“…We believe this is due to regions with high E LAF usually being associated with updrafts containing condensationally narrowed droplet distributions. Low E  being associated with updraft was also found in an observational study of Southern Ocean stratocumulus clouds, albeit only when aerosol loading is low (Wang et al, 2021), in cumulus clouds (Lu et al, 2012), and theoretically based on parcel model simulations (Chen et al, 2016). Additionally, a positive correlation between E LAF and adiabatic fraction (as a measure of the degree of mixing) suggests that turbulent mixing could promote the broadening of droplet spectra, which agrees with past modeling studies (Abade et al, 2018;Lasher-Trapp et al, 2005;Lu & Seinfeld, 2006;Noonkester, 1984).…”
Section: Summary and Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…We believe this is due to regions with high E LAF usually being associated with updrafts containing condensationally narrowed droplet distributions. Low E  being associated with updraft was also found in an observational study of Southern Ocean stratocumulus clouds, albeit only when aerosol loading is low (Wang et al, 2021), in cumulus clouds (Lu et al, 2012), and theoretically based on parcel model simulations (Chen et al, 2016). Additionally, a positive correlation between E LAF and adiabatic fraction (as a measure of the degree of mixing) suggests that turbulent mixing could promote the broadening of droplet spectra, which agrees with past modeling studies (Abade et al, 2018;Lasher-Trapp et al, 2005;Lu & Seinfeld, 2006;Noonkester, 1984).…”
Section: Summary and Discussionsupporting
confidence: 86%
“…If a E N is spatially homogeneous, then these two methods of scaling are identical. Finally, note that since high E LAF is by definition correlated with low , Wang et al (2021).…”
Section: Positive Correlation No Correlationmentioning
confidence: 95%
“…Several observational and modeling studies suggested that the effects of aerosol loading on ϵ partially offset or enhance the aerosol second indirect effect, depending on the sign of the induced change in ϵ (e.g., Liu & Daum, 2002; M.‐L. Lu et al., 2007; G. Martin et al., 1994; Pawlowska et al., 2006; Yeom et al., 2019; Y. Wang et al., 2021). Chen et al.…”
Section: Introductionmentioning
confidence: 99%
“…In turn, these uncertainties impact the calculation of microphysical process rates and therefore the evolution of clouds in the simulations (e.g., Igel & van den Heever, 2017). For example, for a cumulus cloud simulated with bulk microphysics using a kinematic framework, Morrison and Grabowski (2007) G. Martin et al, 1994;Pawlowska et al, 2006;Yeom et al, 2019;Y. Wang et al, 2021).…”
mentioning
confidence: 99%
“…A lot of evidences about the interaction between aerosols and clouds have been found through ground-based remote sensing (Garrett et al, 2004;S. Li et al, 2017;Pandithurai et al, 2009), satellite remote sensing (Costantino & Breon, 2010;Gryspeerdt & Stier, 2012), in-situ observations (Maahn et al, 2017;Y. Wang et al, 2021;Zhao et al, 2018), and model simulations (J.…”
mentioning
confidence: 99%